Evaluation of the independent curriculum in learning Buddhist religious education at elementary school. Waringin Sari Timur Pringsewu - Mila Artika; Sidartha Adi Gautama; Dedi Kundana (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum in Buddhist Religious Education at SD Negeri 3 Waringin Sari Timur Pringsewu. The main objective of this study is to gain an in-depth understanding of the implementation of the curriculum based on the values of the Pancasila Student Profile, particularly in the context of minority religious education. This study also aims to identify the extent to which the Merdeka Curriculum has an impact on the character building of students, as well as how the school supports the facilitation of an inclusive and valuable learning process. This study uses a qualitative approach with an evaluative method based on the CIPP (Context, Input, Process, Product) model. Data collection techniques were carried out through observation, in-depth interviews with the principal, vice principal in charge of curriculum, and Buddhist Education teachers, as well as documentation of learning tools. The CIPP model was used to examine the context of the curriculum policy, the readiness and availability of supporting resources, the learning implementation process, and the results or impact of the curriculum implementation. The results showed that the school had implemented the Merdeka Curriculum gradually in accordance with applicable regulations. Buddhist education was implemented equally and comprehensively, despite facing obstacles in the form of a limited number of official textbooks. The school provided support through training programs such as Tathagata and learning communities. The evaluation of student achievement shows a significant improvement in character, as reflected in the Education Report Card indicators, which improved from the red (poor) category in 2022 to green (good) in 2024–2025. These findings show that the Merdeka Curriculum can be effectively implemented in minority religious education if it is supported by resource readiness and institutional commitment.